PERAN ORANG TUA DALAM PENGUATAN PENDIDIKAN KARAKTER ANAK DI RUMAH - Sastradiharja, Ee Juanedi (Kopertais Wilayah I DKI Jakarta dan Banten, 2018)
Parents have a very important role and function in children's character building. In the family, parents are madrasatul or school first and foremost for children, therefore, parents reinforcement must be able to provide character education for their cihildren at home. The intensity of communication and held face to face is sufficient in order to allow socialization and strengthen character values, morals, and other good behavior can be internalized in children through habitual in everyday life at home.